Solvent-free mechanochemical oxidation and reduction of biomass-derived 5-hydroxymethyl furfural. Issue 23 (9th November 2018) - Chacón-Huete, F.; Messina, C.; Chen, F.; Cuccia, L.; Ottenwaelder, X.; Forgione, P.
Abstract : The simultaneous synthesis of 5-hydroxymethyl-2-furoic acid and 2, 5-hydroxymethylfuran from biomass-derived 5-hydroxymethyl furan was developed using a solvent-free mechanochemical approach. Abstract : The simultaneous synthesis of 5-hydroxymethyl-2-furoic acid and 2, 5-hydroxymethylfuran from biomass-derived 5-hydroxymethyl furan was developed using a solvent-free mechanochemical approach. The results obtained for the Cannizzaro disproportionation reaction show quantitative conversions of the starting materials with reaction times of only 5 min. Employing solvent-free conditions allows for a more sustainable synthetic approach that is reflected in an E factor 7 times smaller than that in previous reports. Additionally, initial results of the use of a sacrificial reagent, with the same solvent-free mechanochemical approach, for the selective reduction and oxidation of HMF are presented.